Commitment of Political Communication in the Mayor of Banda Aceh, Indonesia - Zahari Nurdin (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
The development of political communication relies on multidisciplinary based on concepts in communication, political science, journalism, sociology, psychology, history, rhetoric, and others. This study deals with commitment of political communication in the mayor of Banda Aceh, Indonesia. Constructivism paradigm is used in this study to discuss the perceptions on truth, explanation, beliefs and views about the world. The result shows that the mayor paradigm in building the Banda Aceh city area referred to the concept of the Prophet's development in Medina, and the Aceh Sultanates in building the area. Success in building the country and region are basically fully committed to carrying out and enforcing Islamic law in order to be strong and reside in the souls of the people. Therefore the mayor believes and is committed to continuing to build the city of Banda Aceh as a civil city model that is inseparable from building Islamic law in a consistent manner.